الإدارة بالأهداف وأثرها على الإبداع الإداري في القطاع الحكومي الأردني من وجهة نظر مديري الإدارة الوسطى في مراكز الوزارات - أبو حمور، عنان محمد أحمد (جامعة اليرموك - عمادة البحث العلمي, 2011)
هدفت هذه الدراسة تعرف مستوى تطبيق الإدارة بالأهداف وأثرها على الإبداع الإداري في القطاع الحكومي الأردني من وجهة نظر مديري الإدارة الوسطى في مراكز الوزارات. \ وقد تكونت عينة الدراسة من (229) مدير مديرية في مراكز الوزارات الأردنية. ولتحقيق أهداف الدراسة، فقد أعدت الباحثة استبانة، وبعد تطبيق الأداة وإجراء التحليل الإحصائي المناسب كالمتوسطات الحسابية والانحرافات المعيارية، واختبار "ت"، واختبار (ANOVA)، واختبار الانحدار المتعدد لأسئلة الدراسة والفرضيات والأسئلة المفتوحة، أظهرت النتائج: \ -\ إن مستوى تطبيق "الإدارة بالأهداف" كان بدرجة متوسطة بمتوسط حسابي وقدره (3.53). \ -\ إن مستوى ممارسة "الإبداع الإداري" كان بدرجة متوسطة. بمتوسط حسابي وقدره (3.54)، وكانت مكوناته مرتبة تنازلياً (الإقناع، والطلاقة، والمرونة، وروح المجازفة، والحساسية للمشكلات، والأصالة). \ وقد أظهرت النتائج وجود أثر إيجابي في مستوى تطبيق الإدارة بالأهداف في دعم الإبداع الإداري بكافة مكوناته في مراكز الوزارات الأردنية من وجهة نظر مديري الإدارة الوسطى. \ وبينت نتائج السؤال المفتوح الأول أن من أبرز معوقات تطبيق الإدارة بالأهداف (المحسوبية، وعدم رغبة الإدارة العليا ومساندتها والتزامها بتطبيق نظام الإدارة بالأهداف)، كما أظهرت نتائج السؤال المفتوح الثاني أن من أهم العوامل التي تشجع الإبداع الإداري لدى الموظف هي (الحوافز والمكافآت). في ضوء النتائج التي تمخضت عنها الدراسة، قدمت الباحثة عدداً من التوصيات: \ -\ تقديم الدعم من الإدارة العليا لتبني أسلوب الإدارة بالأهداف في العمل الحكومي. \ -\ تقديم الحوافز والمكافآت بشكل دوري، لدعم الإبداع الإداري في العمل الحكومي. \ -\ إجراء دراسات مقارنة بين القطاع العام والخاص تتناول متغيرات الدراسية الحالية. this study aimed at identifying the impact of management by objectives on managerial innovation as perceived by middle management in the centers of ministries. \ the sample of this study consisted of (229) middle managers in the central offices of Jordanian ministries. In order to achieve the purpose of the study, the researcher prepared a questionnaire. After implementing the instrument of the study and applying the approporiate statistical analysis such as means, standard deviations, (T) test, ANOVA test and multiple regression, on the questions, hypotheses of the study, and the open-ended questions, the following results were obtained: \ 1.\ The level of "management by objectives " was moderate with a mean of (3.53). \ 2.\ The level of practicing managerial innovation was moderate with a mean of (3.54) and its components were descendingly arranged as follows: persuasion, fluency, flexibility, risk spirit, sensitivity to problems and originality. \ \ The findings showed that there was positive impact of management by objectives on managerial innovation as perceived by the sample. \ The findings of the first open-ended question indicated that the most significant constraints on the application of management by objectives are favoritism, and the lack of desire of high-management, its support and commitment to apply management by objectives. Also, the findings of second open-ended question indicated that, the most significant factor to encourage managerial innovation is (incentives and rewards). Based on the results of the study, the following recommendations are made \ 3.\ Support from top management to adapt MBO in governmental work should be provided. \ 4.\ Incentives and rewards periodically should be provided and awareness and knowledge about the significance of organizational loyalty and managerial innovation in governmental work should be increased. \ 5.\ A comparative study between public and private sectors relating to variables of current study should be conducted.
Keywords: مديرو الإدارات -- الإدارة بالأهداف -- الإبداع الإداري -- الحكومة -- الأردن -- الإدارة الوسطى -- الوزارات -- التنظيم الإداري